2014
DOI: 10.3892/or.2014.3247
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D analogs combined with 5-fluorouracil in human HT-29 colon cancer treatment

Abstract: In the present study, we evaluated the antitumor effect of two synthetic analogs of vitamin D, namely PRI-2191 [(24R)-1,24-dihydroxyvitamin D3] and PRI-2205 (5,6-trans calcipotriol), in combined human colon HT-29 cancer treatment with 5-fluorouracil (5-FU). Mice bearing HT-29 tumors transplanted subcutaneously or orthotopically were injected with vitamin D analogs and 5-FU in various schedules. A statistically significant inhibition of subcutaneous or orthotopic tumor growth was observed as a result of combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…These effects appeared to be the consequence of a suppression of gene transcriptional activities and protein expression of survivin and thymidylate synthase, to the enhanced E-cadherin localization in cell membranes and the complex formation of Ecadherin and b-catenin, and repression TCF4 transcriptional activation. Consistent with these observations, on one hand, recent findings by Milczarek et al (2014) showed that calcipotriol may potentiate the antitumor activity of 5-FU in HT-29 colon tumor-bearing mice. These studies also showed that the mechanism of potentiation of 5-FU antitumor was related to the increased expression of p21 and decreased expression of pERK1/2 level which may lead to a decreased expression of thymidylate synthase.…”
Section: Calcipotriolsupporting
confidence: 76%
See 1 more Smart Citation
“…These effects appeared to be the consequence of a suppression of gene transcriptional activities and protein expression of survivin and thymidylate synthase, to the enhanced E-cadherin localization in cell membranes and the complex formation of Ecadherin and b-catenin, and repression TCF4 transcriptional activation. Consistent with these observations, on one hand, recent findings by Milczarek et al (2014) showed that calcipotriol may potentiate the antitumor activity of 5-FU in HT-29 colon tumor-bearing mice. These studies also showed that the mechanism of potentiation of 5-FU antitumor was related to the increased expression of p21 and decreased expression of pERK1/2 level which may lead to a decreased expression of thymidylate synthase.…”
Section: Calcipotriolsupporting
confidence: 76%
“…Experimental observations show that this molecule exerts important effects on cellular differentiation and proliferation in vitro while its effect on calcium metabolism in vivo is negligible (Binderup & Bramm, 1988;Cho et al, 1996). In vitro studies showed that this molecule may regulate cell differentiation and proliferation and exhibits growth-inhibiting effects against several human cancer cell lines including HL-60 and HL60/MX2 promyelocytic leukemia, U937 histiocytic lymphoma, MCF-7, T47D human breast cancer, HT-29 human colon cancer, and human SCC (Colston et al, 1992;Meephansan et al, 2012;Milczarek et al, 2013aMilczarek et al, , 2014. Regarding the possible mechanisms underlying the growth inhibiting and pro-differentiating effects of calcipotriol on tumor cells, in vitro studies highlighted the fact that a 20-h exposure of LNCaP prostate cancer cells and MCF-7 breast cancer cells to this analogue or to BGP-15, a new calcipotriene-derived vitamin D 3 analogue, generated procaspase-3 cleavage and ultimately, apoptosis (Berkovic et al, 2010).…”
Section: Calcipotriolmentioning
confidence: 99%
“…In this paper, we report the differential anti-proliferative responses of pigmented and non-pigmented rodent melanoma cells to classical metabolites of Vitamin D (1,25(OH) 2 D 3 and 25(OH)D 3 ) and novel 20(OH)D 3 [ 61 ] and calcipotriol [ 62 ], as well as short-side chain secosteroids, pD [ 63 ], 20(OH)pD, 20(OH)pL [ 64 ] and 21(OH)pD [ 36 ]. It should be noted that 20(OH)D 3 , pD, 20(OH)pD and 21(OH)pD are non- or low- calcemic secosteroids that may represent therapeutic alternatives to 1,25(OH) 2 D 3 , which is highly calcemic [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…VDR functions as a transcription factor that regulates various biological processes including the regulation of proliferation, differentiation, apoptosis, angiogenesis, immunity and miRNAs ( 9 ). Studies have reported an antineoplastic effect of VDR, particularly in colorectal cancer; VDR expression is increased in well-differentiated or moderately differentiated colorectal cancer tissues, however is decreased in poorly differentiated tumors ( 20 ), and high VDR expression is correlated with an advantageous prognosis in colorectal patients ( 21 ). In addition, studies in different animal models and cell lines of colorectal cancer support the antineoplastic effect of VDR via various mechanisms ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%